Quality service management a guide to improving business processes - Maleyeff, John, 1955- (New York, NY : Routledge, 2022)
Providing clear guidance for anyone servicing internal or external customers, this book offers a framework for analyzing and managing quality using a comprehensive closed-loop approach. This book cuts through the complexities of the mantra better, cheaper, faster' (BCF) and offers procedures for the evaluation of customer needs, the determination of performance metrics, and the design of effective customer satisfaction surveys. It details basic statistical techniques and packages the framework, procedures, and methods into a management construct that includes external quality certification systems and internal performance management systems. Importantly, the book also describes how these systems can be implemented in a virtual workplace. This quality management book will be essential to service-oriented firms (financial, government, healthcare, hospitality, etc.), as well as any firm with internal customer service processes such as human resource management, purchasing, and accounting. Professionals at all levels, corporate trainers, and students will welcome this book's common set of principles and tools, accompanied by many case studies that illustrate how they are applied in various environments.
OCLC-licensed vendor bibliographic record.
Keywords: Reengineering (Management); Management -- Evaluation; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Information Management; BUSINESS & ECONOMICS / Production & Operations Management